THE MEDIATOR EFFECT OF LOGISTICS PERFORMANCE INDEX ON THE RELATION BETWEEN GLOBAL COMPETITIVENESS INDEX AND GROSS DOMESTIC PRODUCT - Mustafa Emre Civelek; Nagehan Uca; Murat Cemberci (European Scientific Journal, ESJ, 2015)
Logistics sector plays a critical role in social and economic developments of a country. Therefore understanding the relationship among the logistic performance, competitiveness and prosperity of a country is important. Logistics Performance Index (LPI) firstly published by World Bank in 2007 and repeated in the years 2010, 2012, 2014. In this research the mediator effect of LPI on the relation between Global Competitiveness Index (GCI) and Gross Domestic Product (GDP) was aimed to analyze for the years 2007, 2010, 2012, 2014. The mediator effect was measured by using hierarchical regression analyses. As a result of the analyses, the mediator effect of LPI on the relation between GCI and GDP was found statistically meaningful. Consequently, the result of the research could be suggested that the logistics ability of a country dominated the relation between competitiveness and prosperity.